Protocolo clínico para cuidado pré-natal no sistema prisional - Abreu, Victórya Suéllen Maciel (2025)
The aim of this study was to adapt clinical guidelines for the construction of a prenatal care clinical protocol for pregnant women deprived of their liberty. This is a methodological study, carried out from March 2024 to February 2025, which followed the recommendations of the ADAPTE tool, with approval by the Research Ethics Committee of the Federal University of Ceará, under opinion number 6.745.715, and will be implemented in the Desembargadora Auri Moura Costa Women's Prison Unit, in the state of Ceará. In the configuration phase, the feasibility of the adaptation was verified and the organization committee and panel were established, with members experienced in prison health research and care, including nurses, a psychologist and a pharmacist. In the adaptation phase, an integrative review was carried out to retrieve guidelines and other guiding materials. Recommendations were adapted from 28 materials, predominantly from the World Health Organization and the Ministry of Health, published in English in 2024. In January 2025, the 9-member panel met in person to make the final decision on the recommendations. The clinical protocol has 11 chapters: Introduction, first prenatal consultation, gestational risk classification and referrals, main complaints, smoking and substance use, immunization, supplements and prophylaxis, physical examination, laboratory tests, imaging tests and educational interventions, and will be used. The use of the AGREE-II tool showed variable methodological quality among the documents, with NICE and WHO guidelines standing out as the most robust references. Comparing the original content with the Brazilian prison context, adjustments were made to ensure applicability, clarity and alignment with national regulations. The main changes included the removal of recommendations incompatible with the prison reality, such as family involvement in prenatal care, the use of tools not validated in Brazil and therapies that are difficult to access. In addition, terminology was standardized, content was reorganized to improve the fluidity of the material and specific adaptations were made for the care of pregnant women deprived of their liberty. The challenges include the scarcity of guidelines aimed at this population and structural barriers that make it difficult to fully implement the recommendations. The adaptation of the guidelines proposes an evidence-based model to qualify prenatal care in prison units, contributing to equity in maternal and child care.